2023
DOI: 10.1302/0301-620x.105b3.bjj-2022-0616.r1
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term survivorship of primary total knee arthroplasty with a specific implant

Abstract: AimsThe purpose of this study was to assess mid-term survivorship following primary total knee arthroplasty (TKA) with Optetrak Logic components and identify the most common revision indications at a single institution.MethodsWe identified a retrospective cohort of 7,941 Optetrak primary TKAs performed from January 2010 to December 2018. We reviewed the intraoperative findings of 369 TKAs that required revision TKA from January 2010 to December 2021 and the details of the revision implants used. Kaplan-Meier a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It aims to contribute to the prosthetic knee’s long-term survivorship by minimizing wear and potential failures, thereby enhancing overall patient quality of life. In particular, it has been previously shown that RA-TKA results in better precision in achieving planned limb alignment and implant positioning than conventional methods [ 27 ]. This precision aims to improve functional outcomes for patients through more physiological joint stability and mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It aims to contribute to the prosthetic knee’s long-term survivorship by minimizing wear and potential failures, thereby enhancing overall patient quality of life. In particular, it has been previously shown that RA-TKA results in better precision in achieving planned limb alignment and implant positioning than conventional methods [ 27 ]. This precision aims to improve functional outcomes for patients through more physiological joint stability and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…A notable limitation of this study is its reliance on short-term follow-up data to formulate conclusions. It is important to recognize that, according to current research, manually implanted TKA demonstrated long-term survivorship (spanning ten to fifteen years) exceeding 90%, particularly when prosthetic failure is attributed to loosening [ 27 , 28 , 29 ]. These studies indicate a commencement of decline in prosthesis survivorship within the short-term follow-up period (3–5 years post-surgery).…”
Section: Discussionmentioning
confidence: 99%